Clampless laparoendoscopic single‐site partial nephrectomy for renal cancer with low PADUA score: technique and surgical outcomes. (29th January 2013) - Springer, Christopher; Veneziano, Domenico; Wimpissinger, Florian; Inferrera, Antonino; Fornara, Paolo; Greco, Francesco
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Laparoendoscopic single‐site (LESS) surgery has proved to be immediately applicable in the clinical field, being safe and feasible in the hands of experienced laparoscopic surgeons in well‐selected patients. All extirpative and reconstructive urological procedures have been described in the literature, but LESS partial nephrectomy (PN) is one of the most complex procedures and few studies have been published on this subject. The study describes a clampless technique for LESS PN, by reducing the blood pressure and increasing the intra‐abdominal pressure of the pneumoperitoneum to 20 mmHg, timed to precisely coincide with excision of the tumour. This technique was found to be safe and feasible in the treatment of low‐risk T1a RCC. Objective To describe the technique and report the surgical outcomes of clampless laparoendoscopic single‐site (LESS) partial nephrectomy (PN) in the treatment of renal cell carcinoma (RCC) with low PADUA score. Patients and Methods Clampless LESS PN was performed in 14 patients with cT1a renal tumours. Indications to perform a clampless LESS PN were low‐risk, laterally based renal tumours, located away from the renal hilum, with a PADUA score ≤7. Demographic data and peri‐operative and postoperative variables were recorded and analysed. Kidney function was evaluated by measuring serum creatinine concentration and estimated glomerular filtration rate (eGFR) pre‐ and postoperatively and at 6‐month follow‐up. Results The median operating time was 120 min and warm ischaemia time was zero in all cases. Only one early complication (Clavien grade 1) was recorded: one patient developed a flank haematoma which it was possible to treat by conservative therapy. Serum creatinine and modification of diet renal disease eGFR were not found to be significantly different pre‐ and postoperatively and at 6‐month follow‐up. Definitive pathological results showed 12 pT1a RCCs and two pT1a‐chromophobe RCCs. All tumours were removed with negative surgical margins. All patients were satisfied with the cosmetic results. At a median (range) follow‐up period of 12 (8–15) months, all patients were alive without evidence of tumour recurrence or port‐site metastasis. Conclusion Clampless LESS PN is a safe and feasible surgical procedure in the treatment of low‐risk T1a RCC, with excellent cosmetic results.